How Large Is the Pay Premium from Executive Incentive Compensation? - Albuquerque, Ana; Albuquerque, Rui; Carter, Mary Ellen; Dong, Qi (The Accounting Review, 2024)
ABSTRACT We estimate the pay premium associated with CEO incentive compensation. Using explicit detailed U.S. CEO compensation contract data and simulation analysis, we find that CEOs with riskier pay packages receive a premium for pay at risk that represents 13.5 percent of total pay. The premium is positively correlated with proxies for CEO risk aversion, but implied risk aversion values suggest that the premium is economically smaller than suggested by prior studies. We perform our tests using a variety of proxies to measure the variance of pay and find consistent evidence of economically small pay risk premiums. These results are consistent with recent findings suggesting that risk may have a more limited influence over the level of pay than previously thought. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: D81; G30; J33.